2017
DOI: 10.1371/journal.pone.0176641
|View full text |Cite
|
Sign up to set email alerts
|

Production of IgG antibodies to pneumococcal polysaccharides is associated with expansion of ICOS+ circulating memory T follicular-helper cells which is impaired by HIV infection

Abstract: Dysfunction of T follicular-helper (TFH) cells is a possible cause of impaired germinal centre (GC) and IgG antibody responses in individuals with human immunodeficiency virus-1 (HIV-1) infection and might contribute to decreased magnitude and isotype diversification of IgG antibodies to pneumococcal polysaccharides (PcPs). We examined the production of IgG1 and IgG2 antibodies to PcPs 4, 6B, 9V and 14 by enumerating antibody secreting cells (ASCs) at day (D) 7 and determining fold-increase in serum antibody l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 76 publications
2
33
0
Order By: Relevance
“…17,18 In untreated HIV-1-infected patients, an increase in T FH cells in the lymph nodes has been associated with both viraemia and hypergammaglobulinaemia. [20][21][22] By contrast, in a small fraction of patients who spontaneously controlled HIV-1 replication, the maintenance of a high frequency of functional cT FH cells able to induce broadly neutralizing antibodies (bNabs) against different HIV-1 strains is critical to avoid disease progression. [20][21][22] By contrast, in a small fraction of patients who spontaneously controlled HIV-1 replication, the maintenance of a high frequency of functional cT FH cells able to induce broadly neutralizing antibodies (bNabs) against different HIV-1 strains is critical to avoid disease progression.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…17,18 In untreated HIV-1-infected patients, an increase in T FH cells in the lymph nodes has been associated with both viraemia and hypergammaglobulinaemia. [20][21][22] By contrast, in a small fraction of patients who spontaneously controlled HIV-1 replication, the maintenance of a high frequency of functional cT FH cells able to induce broadly neutralizing antibodies (bNabs) against different HIV-1 strains is critical to avoid disease progression. [20][21][22] By contrast, in a small fraction of patients who spontaneously controlled HIV-1 replication, the maintenance of a high frequency of functional cT FH cells able to induce broadly neutralizing antibodies (bNabs) against different HIV-1 strains is critical to avoid disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…23 This phenomenon has been linked to a large number of mutations in variable IgG regions due to the process of somatic hypermutation. 21,25 Since damage in the T FH -cell compartment is an event observed during the acute phase of HIV-1 infection, early antiretroviral (ARV) therapy enables the preservation of T FH function. 22,24 Furthermore, as expected, the maintenance of functional cT FH cells is also associated with a better response to various vaccines in HIV-1-infected patients.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Effective protection of immunocompromised individuals against IPD remains a challenge as highlighted in previous sections. It was found that specific adaptive immune cells such as T follicular cells (Tfh) were important for antibody production in response to pneumococcal polysaccharide vaccination [93] but that this was impaired during HIV-infection, whereas an extra PCV13 booster could provide additional benefit among immunocompromised individuals [94].…”
Section: Immunologymentioning
confidence: 99%